A systematic evaluation for the potential translation of CD166-related expression as a cancer biomarker. (1st September 2016) - Xiao, Meng; Wang, Xu; Yan, Ming; Chen, Wantao
ABSTRACT: Introduction : Many basic studies have provided some evidences for the correlations of CD166 to cancer. However, along with the growing studies on the clinical values of CD166 in cancer areas, some controversial and inconclusive results were obtained. Areas covered : An appropriate query and collection of the published articles was conducted through search in PubMed and EMBASE database. A subsequent systematical and quantitative summary of CD166 related expression and cancer was conducted with meta-analysis to clarify its clinical significance for potential translation as cancer biomarkers. Expert commentary : The overall results suggested total CD166 correlated to cancer risk, membrane CD166 correlated to nodal metastasis and cytoplasmic CD166 correlated to TNM stage, and disease-free survival. The membrane CD166, cytoplasmic CD166 and soluble CD166 showed great potential to be used as a panel of markers for predicting cancer overall survival. We might conclude that CD166 functions as a risk factor for cancers, and the alterations of its different functional isoforms were observed to correlate with specific or interplayed clinical outcomes.